Antimicrobial Activity of Extracts from In Vitro Mycelia Culture-Derived Sclerotia of Sclerotium rolfsii - Nyochembeng, Leopold M.; Holloway, Isis; Hopkinson, Sampson (International Journal of Bio-resource and Stress Management, 2023)
Sclerotium rolfsii is a soil-borne fungal pathogen that causes southern blight disease on a wide range of agricultural and horticultural crops. During colonization of host tissue, it produces a considerable mass of vigorous mycelia on the plant’s surface leading to tissue decay and subsequent production of sclerotia. S. rolfsii is also known to produce sclerotial exudates which are thought to help the fungus survive. Analyzing the sclerotial extract (SCE) for anti-microbial activity potentially, may lead to the development of a biopesticide for disease control. To achieve this, we evaluated five different fungal culture media for sclerotia production in the laboratory and assayed for antifungal and antibacterial activities of the sclerotial extract on various plant pathogens. Sclerotia production (quantity and weight) was significantly greater in oatmeal agar (OMA) than in potato dextrose agar (PDA), V8 juice, cornmeal agar (CMA) and 2% water agar (WA). The mean diameter of sclerotia produced in PDA and OMA was similar but significantly greater than that of sclerotia produced in other media. Antimicrobial assays of the water-soluble sclerotial extracts showed that they reduced the growth of Leptosphaeria maculans and Ralstonia solanacearum, significantly inhibited the growth of Xanthomonas campestris pv vesicatoria and completely inhibited the growth of Erwinia amylovorain the laboratory. The minimum inhibitory concentrations (MIC) of the extracts were 10% and 25% for E. amylovora and X. campestris pv vesicatoria respectively. These results indicate that oatmeal agar is suitable for sclerotia production in the laboratory and that S. rolfsii SCE has considerable antimicrobial activity against some plant pathogenic fungi and bacteria.